2003
DOI: 10.1677/erc.0.0100359
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian stanniocalcins and cancer.

Abstract: Stanniocalcin (STC) is a glycoprotein hormone that is secreted by the corpuscle of Stannius, an endocrine gland of bony fish, and is involved in calcium and phosphate homeostasis. The related mammalian proteins, STC1 and STC2, are expressed in a wide variety of tissues. The ovaries have the highest level of STC1, and this increases during pregnancy and lactation. STC1 is present in breast ductal epithelium, and its expression is induced by BRCA1, a tumor suppressor gene that has an important role in breast and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
133
0
10

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(147 citation statements)
references
References 98 publications
4
133
0
10
Order By: Relevance
“…Ataxin 1 is detected in various brain regions and in non-neuronal tissues, such as the heart, skeletal muscle and liver (Servadio et al, 1995;Tsai et al, 2004). Stanniocalcin1, encoded by STC1 gene, is a glycoprotein hormone and it has a role in many physiological processes, including bone development, reproduction, wound healing, angiogenesis and modulation of inflammatory response (Ishibashi and Imai, 2002;Chang et al, 2003). The STC1 gene is expressed in a wide variety of tissues, including the kidney, prostate, thyroid, bone and ovary (Chang et al, 1995;Olsen et al, 1996;Varghese et al, 1998).…”
Section: Atxn1 and Stc1 Are Targets Of Mir-101bmentioning
confidence: 99%
“…Ataxin 1 is detected in various brain regions and in non-neuronal tissues, such as the heart, skeletal muscle and liver (Servadio et al, 1995;Tsai et al, 2004). Stanniocalcin1, encoded by STC1 gene, is a glycoprotein hormone and it has a role in many physiological processes, including bone development, reproduction, wound healing, angiogenesis and modulation of inflammatory response (Ishibashi and Imai, 2002;Chang et al, 2003). The STC1 gene is expressed in a wide variety of tissues, including the kidney, prostate, thyroid, bone and ovary (Chang et al, 1995;Olsen et al, 1996;Varghese et al, 1998).…”
Section: Atxn1 and Stc1 Are Targets Of Mir-101bmentioning
confidence: 99%
“…S6). Further knockdown of this transcript was not achievable in stable cell lines, perhaps owing to the pro-proliferative function of this gene (12). Importantly, the stable knockdown of STC1 did not alter PR-B expression in either cell line (Fig.…”
Section: Hormone-independent Pr Target Genes Contribute To Breast Cancermentioning
confidence: 95%
“…1C and S1), we investigated the regulation of selected endogenous gene targets by unliganded PR. Stanniocalcin 1 (STC1), a peptide hormone overexpressed in breast cancers, has been shown to increase cell metabolism and tumor growth (12). Gene array analysis of T47D breast cancer cells demonstrated that STC1 expression is induced by the forced expression of unliganded PR-A or PR-B (7).…”
Section: Sumoylation Of Pr-b Represses Transcription Of a Subset Of Tmentioning
confidence: 99%
“…Many independent studies have reported alterations in STC1 expression levels in response to different stresses (Iyer et al, 1999;Sheikh-Hamad et al, 2000;Chang et al, 2003), but the significance of such changes in expression has hitherto been unknown. In light of our findings, it appears that STC1 functions in response to cellular stress to control the cell death vs survival decision, and this is consistent with two recent studies.…”
Section: Regulation Of Oxidative Stress Response By Stc1mentioning
confidence: 99%
“…Stanniocalcin-1 (STC1) is a glycoprotein that has been highly conserved from fish to mammals (Chang et al, 2003). In fish, it functions as a classic hormone that is secreted from endocrine glands, the Corpuscles of Stannius, in response to hypercalcemia and inhibits uptake of calcium through the gills and gut (Wagner et al, 1988;Sundell et al, 1992).…”
Section: Introductionmentioning
confidence: 99%